Hunting in the Holy Quran: A Semantic Study - Prof. Ghazi Mutasher Hamza Al-Badri (Journal of College of Education, 2026)
Anyone who contemplates the Quranic text will realize that Allah Almighty has placed every word, indeed every letter, in His Noble Book with an intentional artistic placement. This placement did not consider the verse alone, nor the surah alone, but rather the entire Quranic text. Allah Almighty has made clear in His Noble Book that He has made this earth and what is on it a source of income for humankind to benefit from as it pleases, in accordance with legal regulations. One of the means by which these gains are achieved is the profession of "hunting," which is the foundation upon which it is based, as it is one of the many blessings of Allah Almighty bestowed upon His servants. It is worth noting that the word "hunting" is only mentioned four times in the Holy Quran, in Surat Al-Ma’idah, referring to what adorns the table. It is one of God Almighty’s countless blessings, as people benefit from it as sustenance for their meals, and they also have other purposes through it. The Holy Quran has divided this profession into two categories: the first is land hunting, which refers to animals and birds hunted on land, not in water, and which no one owns. However, Al-Zamakhshari limited this category to those that live on land or in water. The second category is marine hunting, which refers to the hunting of fish and whales in seas, oceans, rivers, and streams. The Holy Quran has emphasized that The basic principle of this profession is permissibility, and the prohibition is its branch, which is that anything a person can reach with his hand, spear, or any of his weapons and kill is considered game. No one may prohibit it except with evidence from the Holy Quran.